NEUTRALITY OF BBC ONLINE NEWSPAPER ON PALESTINE-ISRAEL WAR BASED ON THE USED OF EUPHEMISM AND DYSPHEMISM - Abidin, Azizah Ivana; Sukaesih, Ina; Wulandari, Linda Sari (Politeknik Negeri Jakarta, 2024)
This research analyzed the Indonesia-English translation in journalistic text, which was published in BBC Online Newspaper. This research analyzed euphemism and dysphemism in journalistic text from BBC Online Newspaper covering the Palestine-Israel war from February to March 2024. This research aims to find out the use of euphemism and dysphemism in BBC Online Newspaper, the translation technique, and the translation quality. This research uses descriptive qualitative methods, purposive sampling techniques, FGD and content analysis, and cultural theme analysis. This study found that between euphemism and dysphemism, euphemism is the dominant diction in a total of 47 data with indirection as the most used with 12 data with the rest in sequence is understatement with 10 data, litotes with 5 data, abstraction with 7 data, semantic shift and metaphorical transfer both with 4 data and widening with 3 data while the dysphemism is 24 data in total. The translation quality is 2.61 from the range of score of 1 to 3, which is considered an accurate translation